Manifestazioni di creatività “imprevista” nell’arte delle donne in Italia negli anni Settanta. Ketty La Rocca e Irma Blank: operare tra gesto e linguaggio - Caterina Iaquinta (Annali Online dell'Università di Ferrara. Sezione Lettere)
The paper analyses the Italian historical-artistic context in the Seventies with reference to the role played by women. The most debated issues surrounding the manifestation of female creativity are reinterpreted in a performative key, understood as a form of gesture.